Evaluation of the insulin-dependent and -independent hypoglycemic effects and understanding their breakdown in the progression of obesity using mice - Fusako Kojima; So Morishita; Shinsuke Uda; Noriko Yutsudo; Yoshihiro Ogawa; Hiroyuki Kubota (PLoS ONE, 2025)
Temporal changes in blood glucose levels are useful in assessing glucose tolerance. While blood glucose levels are known to be tightly regulated by insulin-dependent and -independent (glucose effectiveness) hypoglycemic effects, their temporal changes and the organs involved have not been sufficiently explored. This study showed how the relative strengths of these effects change over time during the glucose clamp test, using biological experiments and a mathematical model. We found that the glucose effectiveness exhibited a transient effect within 60 min, whereas the insulin-dependent effect showed a sustained effect intensified after 60 min. Additionally, we found that the liver and muscles were responsible for glucose effectiveness and insulin-dependent hypoglycemic effects, respectively. We applied this model to obese mice and found that both hypoglycemic effects decreased as obesity progressed. These results provide insights into hypoglycemic effects and have important implications for the assessment and interpretation of glucose tolerance in mice.